Photocatalyzed Functionalization of Alkenoic Acids in 3D‐Printed Reactors. Issue 17 (8th July 2022) - Jorea, Alexandra; Ravelli, Davide; Romarowski, Rodrigo M.; Marconi, Stefania; Auricchio, Ferdinando; Fagnoni, Maurizio
Abstract: The valorization of alkenoic acids possibly deriving from biomass (fumaric and citraconic acids) was carried out through conversion in important building blocks, such as γ‐keto acids and succinic acid derivatives. The functionalization was carried out by addition onto the C=C double bond of radicals generated under photocatalyzed conditions from suitable hydrogen donors (mainly aldehydes) and by adopting a decatungstate salt as the photocatalyst. Syntheses were performed under batch (in a glass vessel) and flow (by using 3D‐printed reactors) conditions. The design of the latter reactors allowed for an improved yield and productivity. Abstract : Biomass valorization : Alkenoic acids were smoothly converted into valuable γ‐keto acids and succinic acid derivatives by decatungstate photocatalyzed addition of selected hydrogen donors (e.g. aldehydes). The adoption of flow conditions and of a 3D‐printed reactor allowed to form the derivatized products in up to quantitative yield with a productivity of ≈15 mmol day −1 .